2021
DOI: 10.1111/mec.15862
|View full text |Cite
|
Sign up to set email alerts
|

Locus‐specific introgression in young hybrid swarms: Drift may dominate selection

Abstract: The rate of hybridization between closely related species that have recently come into secondary contact is increasing, due to human-assisted migration and environmental change (Grabenstein & Taylor, 2018;Parmesan & Yohe, 2003). While such hybridization is not necessarily negative (Hamilton & Miller, 2016), in many cases hybridization can cause problems for native species. If F1s are

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 69 publications
2
48
0
Order By: Relevance
“…Additionally, Bayesian genomic clines, which can be used to compare the rate and extent of introgression in hybrid populations ( Gompert and Buerkle 2011 ; Gompert and Buerkle 2012 ), were used to quantify locus-specific introgression. We found that red deer and sika in Scotland are quite genetically diverged, with a genome-wide F st of 0.532 (95% confidence interval: 0.529–0.534; McFarlane et al 2020 ), although it should be noted that there is substantial variation in divergence across the genome ( McFarlane et al 2021 ). We also found substantial variation in the rate of introgression, indicating the potential for some SNPs to be under selection ( McFarlane et al 2021 ).…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Additionally, Bayesian genomic clines, which can be used to compare the rate and extent of introgression in hybrid populations ( Gompert and Buerkle 2011 ; Gompert and Buerkle 2012 ), were used to quantify locus-specific introgression. We found that red deer and sika in Scotland are quite genetically diverged, with a genome-wide F st of 0.532 (95% confidence interval: 0.529–0.534; McFarlane et al 2020 ), although it should be noted that there is substantial variation in divergence across the genome ( McFarlane et al 2021 ). We also found substantial variation in the rate of introgression, indicating the potential for some SNPs to be under selection ( McFarlane et al 2021 ).…”
Section: Introductionmentioning
confidence: 69%
“…We found that red deer and sika in Scotland are quite genetically diverged, with a genome-wide F st of 0.532 (95% confidence interval: 0.529–0.534; McFarlane et al 2020 ), although it should be noted that there is substantial variation in divergence across the genome ( McFarlane et al 2021 ). We also found substantial variation in the rate of introgression, indicating the potential for some SNPs to be under selection ( McFarlane et al 2021 ). If there is an SNP for carcass mass that is in a causal region, or in linkage disequilibrium (LD) with a causal region, we should have high power to detect it, based on the F st between red deer and sika, the large phenotypic divergence and the estimated number of generations since admixture began (approximately 6–7; Crawford and Nielsen 2013 ; McFarlane et al 2020 ).…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations